Pengaruh Kesulitan Keuangan, Perjanjian Hutang, dan Harga Transfer terhadap Penghindaran Pajak yang Dimoderasi Kepemilikan Asing - Salsabila Salsabila; Nera Marinda Machdar (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
In Indonesia, the effort to maximize tax revenue is not without obstacles. In the process of tax reform carried out by the government, differences in the interests of the government and the business world become apparent. The existence of these differences causes tax avoidance by the taxpayer. Researchers made this scientific article, aiming to examine and examine the effect of financial difficulties, debt agreements and transfer prices on tax avoidance moderated by foreign ownership. This study uses a qualitative descriptive method to examine a phenomenon by describing the data obtained from literature studies. The results of this study indicate that the variables of financial difficulties, debt agreements, and transfer prices affect tax avoidance. As well as financial difficulties, debt agreements, and transfer prices are able to be moderated by foreign ownership on tax avoidance.